1990
DOI: 10.7882/az.1990.005
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Habitat by Roads and Utility Corridors: A Review

Abstract: This review the ecological effects of roads and utnity corridors such as powerlines, pipelines, canals .!Iod railway lines on undisturbed habittlt .!Iod native wildlife. Public concern about roads in natural areas is increasing, as shown by the public protesls Clgainst forest roads in tile Central Highlands of Vlctorie and tile National Estate areas in the south-east forests of New South Wales. The Daintree Road through Queensland's tropical rainforest crco!Ited an international protest and remains Australia's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
1
18

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(152 citation statements)
references
References 59 publications
0
122
1
18
Order By: Relevance
“…Generalist predators are thought to benefit from fragmented landscapes through increased visibility and mobility in disturbed areas, access to a broad range of food sources, and exploitation of edge habitats (Andrews 1990, Harrison and Bruna 1999, Buskirk 2000, Gehring and Swihart 2003. Indeed, Andrén et al (1985) observed that the density of generalist corvid birds was higher south of the boreal zone in Sweden where cycles of tetraonid birds disappear, and was positively correlated with dummy nest predation rate, fragmentation degree of forests, and proportion of agricultural lands.…”
Section: Table Of Contents List Of Figuresmentioning
confidence: 99%
“…Generalist predators are thought to benefit from fragmented landscapes through increased visibility and mobility in disturbed areas, access to a broad range of food sources, and exploitation of edge habitats (Andrews 1990, Harrison and Bruna 1999, Buskirk 2000, Gehring and Swihart 2003. Indeed, Andrén et al (1985) observed that the density of generalist corvid birds was higher south of the boreal zone in Sweden where cycles of tetraonid birds disappear, and was positively correlated with dummy nest predation rate, fragmentation degree of forests, and proportion of agricultural lands.…”
Section: Table Of Contents List Of Figuresmentioning
confidence: 99%
“…It has been widely accepted that the construction of roads has the potential to facilitate the ingress of predators (including carnivorous mammals, birds and reptiles) into forest environments previously inaccessible to them (Andrews 1990;Fanning and Mills 1990;Gilmore 1990;Copson 1991) or, at least, that the use of roads by feral predators for hunting and movement is commonplace since roads provide easy travelling conditions (Bennett 1990;Cunningham 1990;Lumsden et al 1991). Andrews (1990) proposed that feral animals are easily introduced into areas where there are roads, as the accompanying edge effect favours species with generalised ecological requirements. Arnold et al (1987) reported that the narrow roadside verges in Western Australia are characterised by weeds and feral animals.…”
Section: Roadsmentioning
confidence: 99%
“…Algunos autores comentan que cuando la vegetación se encuentra en recuperación algunas poblaciones tienden a recolonizar nuevamente el área (Hanski 1994). Otros autores mencionan que en los estados secundarios, la presencia de caminos y veredas constituyen pequeños ecotonos, que a su vez concentran una elevada cantidad de organismos por presentar características apropiadas para su movilización (Andrews 1990). Contrariamente a estas teorías y a la teoría de la perturbación media (Connel 1978), los resultados encontrados mediante el muestreo sistemático muestran que los estados menos perturbados fueron los que registraron mayor número de especies.…”
Section: Prueba Para Diferencias Entre Grupos Edad Vegetaciónunclassified